Effect of fertigation on growth, yield, fruit quality and leaf nutrients content of strawberry (Fragaria x ananassa) cv Chandler - KACHWAYA, DILIP SINGH; CHANDEL, J S (The Indian Journal of Agricultural Sciences, 2015)
A field experiment was conducted during 2011-12 to study the performance of different levels of fertigation and soil fertilization on growth, yield, fruit quality and leaf nutrients content of strawberry (Fragaria × ananassa Duch.). The experiment was laid out in randomized block design with five fertigation treatments, viz. (T1) recommended dose of NPK through soil, (T2) recommended dose of NPK through drip, (T3) ¾ of recommended dose of NPK through drip, (T4) ½ of recommended dose of NPK through drip and (T5) 1/3 of recommended dose of NPK through drip and each treatment was replicated five times. The healthy runners of cv. Chandler were planted at a spacing of 25 cm × 50 cm in well prepared beds of 2 m × 2 m size in the last week of September 2011 and 2012 as the crop was taken as annual crop. The results revealed that fertigation with recommended dose of NPK gave significantly higher plant height (24.23 cm), leaf area (129.20 cm2), fruit yield (35.64 tonnes/ha) as compared to fertigation with ½ and 1/3 of recommended dose of NPK and soil fertilization, but was found at par with ¾ recommended dose of NPK fertigation treatment. The maximum fruit length (42.49 mm), fruit breadth (31.74 mm) and fruit weight (19.87 g) was also recorded in fertigation with full recommended dose of NPK. The values of TSS (9.88oB), total sugar (9.44%), anthocyanin (0.249 OD) and ascorbic acid (53.39 mg/100g) was significantly higher in fertigation with recommended dose of NPK treatment as compared to lower levels of fertigation and soil fertilization. The plants fertigated with full and ¾ recommended dose of NPK also had higher leaf nutrients content. Fertigation with ¾ of recommended dose of NPK registered 60 per cent higher fertilizer use efficiency over soil fertilization with full recommended dose of NPK and also resulted in 25 per cent saving of fertilizers without any adverse effect on growth, yield and fruit quality.